Experiments imaginaries desires: Searching for a space of resistance - Lundin, Jessica; Palo, Pia (My University, 2023)
In recent decades, the dominant paradigm of top-down, profit driven urban development has been institutionalized and dogmatized by decision makers in cities. It leaves no space for alternative imaginaries, but rather tries to exert full control over the definition of how cities should be developed and used. As a means of resistance, this thesis argues for the need of the disorderly, for ambiguous urban spaces characterized by being messy, rough, and uncontrolled. The thesis is situated in the specific context of Lundbystrand, an ex-industrial area of central Gothenburg that is being transformed into a cluster for tech and automotive industries. Market-driven development has led to demands for an ordered, clean, safe, and tidy urban form that conflict with spontaneous appropriation of space and bottom-up initiatives. In response to this, the thesis challenges the conception of what you can do, and who can interfere in the public realm. It aims to convince of something most do not seem to agree with: that the messy, rough, and uncontrolled are spatial qualities that have positive human and non-human value. This is done through an exploration of the potential values of the disorderly, with a particular focus on ambiguity and the feeling of allowance that it creates. The overarching approach is to embrace the uncertainty and complexity that make up the world, drawing on assemblage thinking and relationscaping. By exploring methods that focus on subjective experiences and recognizes more-than-human ways of thinking, the work investigates the role of micro-scale design experiments in provoking desires and other models of shaping the city. Rather than resulting in a design proposal, the thesis shows how experimental design processes can generate capacity to produce collective and individual imaginaries and actions, initiating a dialogue about whose desires dictate the visions of the future. The outcome is a contribution to an alternative spatial interpretation of Lundbystrand, with three on-site design experiments that transform and are transformed by the shifting assemblages they engage with.
Keywords: Ambiguous space; Assemblages; Micro-scale; Relationscaping; Urban design